The Political Economy of Development: An Assessment. - Adam, C; Dercon, S (Oxford University Press, 2009)
Research in the field of economic development is increasingly engaged with questions of political economy, of how political choices, institutional structures, and forms of governance influence the economic choices made by governments and citizens. We summarize recent developments in the field and introduce a set of papers that illustrate key themes and methodological innovations associated with the 'new' political economy of development.